Secure and Efficient User Authentication Scheme in Ubiquitous Wireless Sensor Networks - Jun-Sub Kim; Jin Kwak (International Journal of Distributed Sensor Networks)
The user authentication scheme in ubiquitous wireless sensor networks (WSNs) is an important security mechanism that allows users to access sensors through wireless networks. Therefore, many user authentication schemes in ubiquitous WSNs have been proposed. However, many user authentication schemes are vulnerable to impersonation attacks, parallel session attacks, password guessing attacks, stolen smart card attacks, and so forth. In this paper, we propose a secure and efficient user authentication scheme for use in ubiquitous WSNs. Our proposed scheme is secure against various attacks and provides mutual authentication and session key establishment. Furthermore, our proposed scheme is efficient at using the hash function and exclusive-OR operation.